Polyimides based on aromatic diisocyanates containing pendent flexible alkoxy chains and aromatic dianhydrides: synthesis, characterization, and liquid-crystal alignment properties - Sarkar, Anjana; Halhalli, Mahadeo R.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2009)
Four new aromatic diisocyanates containing pendent flexible alkoxy chains, namely, 5-butyloxy-1,3-phenylenediisocyanate, 5-octyloxy-1,3-phenylenediisocyanate, 5-dodecyloxy-1,3-phenylenediisocyanate, and 5-hexadecyloxy-1,3-phenylenediisocyanate, were synthesized by Curtius rearrangement of the corresponding 5-alkoxy-1,3-phenylene diacylazides. These diisocyanates were each polycondensed with three commercially available aromatic dianhydrides: 4,4'-oxydiphthalic anhydride, 3,3',4,4'-(hexafluoroisopropylidene) diphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride-in benzonitrile in the presence of 1,4-dizabicyclo[2.2.2]octane as a catalyst to obtain a series of polyimides with inherent viscosities in the range 0.16-0.43 dL/g. Except for 3,3',4, 4'-benzophenonetetracarboxylic dianhydride based polyimides, all of the polyimides were found to be soluble in dichloromethane, m-cresol, 1-methyl-2-pyrrolidinone, tetra-chloroethane, and pyridine either at room temperature or on heating and could be cast into tough, flexible, transparent films from a solution in in-cresol or tetra chloroethane. X-ray diffractograms revealed that the polyimides with longer alkoxy chains had layered structures. The glass-transition temperature of the polyimides containing pendent flexible alkoxy chains were in the range 159-246 degrees C as measured by differential scanning calorimetry. The temperature for the 10% weight loss of the polyimides was in the range 410-460 degrees C in a nitrogen atmosphere, which indicated good thermal stability. A pretilt angle of 2.97 degrees was observed for the polyimide derived from 5-octyloxy-1,, 3-phenylenediisocyanate and 4,4'-oxydiphthalic anhydride. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 461-472, 2009
Keywords: High performance polymers; polyimides; Thermal properties

Synthesis and characterization of new polyimides containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Halhalli, Mahadeo R.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
A new unsymmetrical aromatic diamine, viz., 4-pentadecylbenzene-1,3-diamine was synthesized through a series of reaction steps starting from 3-pentadecylphenol. 4-Pentadecylbenzene-1,3-diamine was employed to synthesize a series of new polyimides by one-step polycondensation in m-cresol with four commercially available aromatic dianhydrides. viz., 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone-tetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA). Inherent viscosities of resulting polyimides were in the range 0.33-0.67 dL/g and number average molecular weights were in the range 14,700-52,200 (GPC, polystyrene standard). Polyimides containing pendent pentadecyl chains were soluble in organic solvents such as chloroform, m-cresol, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone (NMP), pyridine and nitrobenzene. Strong and flexible films of polyimides could be cast from their chloroform solutions. Polyimides exhibited glass transition temperature in the range 158-206 degrees C. The temperature at 10% wt. loss (T(10)). determined by TGA in nitrogen atmosphere, of polyimides was in the range 470-480 degrees C indicating good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; Glass transition temperature; Pendant pentadecyl chain; polyimides

Novel poly(amide-hydrazide)s and copoly(amide-hydrazide)s from Bis-(4-aminobenzyl) hydrazide and aromatic diacid chlorides: synthesis and characterization - Medhi, M.; Patil, A. S.; Halhalli, Mahadeo R.; Choubey, A.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Applied Polymer Science, 2010)
A new aromatic diamine, viz., bis-(4-aminobenzyl) hydrazide (BABH), which contains preformed hydrazide and methylene linkage, was synthesized starting from alpha-tolunitrile. The BABH and intermediates involved in its synthesis were characterized by spectroscopic methods. Novel poly(amide-hydrazide)s were synthesized by low temperature solution polycondensation of BABH with isophthaloyl chloride (IPC) and terephthaloyl chloride (TPC). Furthermore, two series of copoly(amide-hydrazide)s, based on different mol % of BABH and bis-(4-aminophenyl) ether (ODA) with IPC/TPC were also synthesized. Poly(amidehydrazide)s and copoly(amide-hydrazide)s were characterized by inherent viscosity [eta(inh)], FTIR, solubility, X-ray diffraction (MUD), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The polycondensation proceeded smoothy and afforded the polymers with inherent viscosities in the range of 0.18-093 dL/g in (NMP + 4% LiCl) at 30 degrees C +/- 0.1 degrees C. These polymers dissolved in DMAc, NMP or DMSO containing LiCl. The solubility of copolymers was considerably improved in line with less crystalline nature due to random placement of constituent monomers during the copolymerization. XRD data indicated that poly(amide-hydrazide)s from BABH alone and IPC/TPC had higher crystallinity than the corresponding copoly(amide-hydrazide)s derived from a mixture of BABH and bis-(4-aminophenyl) ether (ODA). Polymers showed initial weight loss around 160 degrees C which is attributed to the cyclodehydration leading to the formation of corresponding poly(amide-oxadiazole)s. Copolyamide-hydrazides showed, T(max) between 400 and 540 degrees C which is essentially the decomposition of poly(amide-oxadiazole)s. (C) 2010 Wiley Periodicals, Inc. J App Polym Sci 116: 2441-2450, 2010
Keywords: bis-(4-aminobenzyl) hydrazide; poly(amide-hydrazide); structure-property relations; Thermogravimetric analysis (TGA); x-ray diffractograms